Controllable porosity conversion of metal-organic frameworks composed of natural ingredients for drug delivery. Issue 55 (27th June 2017) - Liu, Jiang; Bao, Tian-Yi; Yang, Xi-Ya; Zhu, Pei-Pei; Wu, Lian-He; Sha, Jing-Quan; Zhang, Lei; Dong, Long-Zhang; Cao, Xue-Li; Lan, Ya-Qian
Abstract : Two extremely rare β-cyclodextrin (β-CD) supported metal-organic frameworks (MOFs), CD-MOF-1 and CD-MOF-2, were induced to crystallize for the first time through a template-induced approach. Abstract : Two extremely rare β-cyclodextrin (β-CD) supported metal-organic frameworks (MOFs), CD-MOF-1 and CD-MOF-2, were induced to crystallize for the first time through a template-induced approach. The targeted CD-MOFs were employed to perform controlled drug delivery and cytotoxicity assays that confirmed their favourable biological potential of being used as drug carriers.